Predicting the outdoor performance of flat-plate III–V/Si tandem solar cells - Liu, Haohui; Ren, Zekun; Liu, Zhe; Aberle, Armin G.; Buonassisi, Tonio; Peters, Ian Marius (Solar Energy, 2017)
In this work, we use a systematic way to calculate and analyze the outdoor performance of flat-plate III–V/Si tandem solar cells, which are promising candidates for next generation 1-Sun PV applications. We use the actual power harvesting efficiency as a measure of outdoor performance. We calculate the difference between harvesting efficiencies and efficiency under standard testing condition for various tandem configurations under Singapore's and Denver's operating conditions. The difference translates into their attainable performance ratios (PR), which is the ratio between actual yield and target yield. The losses due to the effect of spectrum, irradiance level, and operating temperatures are analyzed and broken down. Calculations show that tandem solar cells do not necessarily suffer more from variations in outdoor conditions than single-junction solar cells. Four-terminal tandem devices can attain higher PR than conventional single-junction Si solar cells. Two-terminal tandem devices designed for standard testing condition suffer from severe current mismatch in Singapore, but still achieved PR on par with single-junction Si solar cells due to better temperature performance. This can be further improved by customization of sub-cell thickness, which is found to reduce current mismatch loss and bring about 0.8–1.7% gain in the final yield.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Energy yield calculation; Performance ratio; Si based tandem solar cells